Nickel ion coupled counter complexation and decomplexation through a modified supported liquid membrane system. Issue 48 (28th May 2015) - Talebi, Amir; Teng, Tjoon Tow; Alkarkhi, Abbas F. M.; Ismail, Norli
<x xml:space="preserve">Abstract</x> Complexation and decomplexation stoichiometry between nickel and D2EHPA in an SLM system are determined, confirmed by Job's method and loading test.